Caracterização do nanocompósito de Al2O3 com inclusões nanométricas de ZrO2 visando sua aplicação como reforço em próteses odontológicas de cerâmica livre de metal - Pierri, Juliano de (2008)
There are many different materials used in dental prosthesis, metal combined with ceramic (metalloceramic), combination of polymers with metal (metal-polymer), metal, polymer and ceramic metal free or metal-free. Metalfree dental prostheses, including crowns and bridges, are attractive to dentists and patients because they have better aesthetics, abrasion resistance, biocompatibility and low thermal conductivity when compared with traditional metal-ceramic prostheses. However, mechanical failures may occur because they are fragile materials. Zirconia (ZrO2) and alumina (Al2O3) are ceramics that have mechanical and aesthetic features suitable for manufacture of these prostheses. In the late 80's, were obtained significant improvements in mechanical properties of composites consisting of alumina matrix with nanoscale inclusions. Previous experimental results showed that the addition of small amounts of nanometric zirconia to the alumina sets a material with interesting mechanical properties. This study proposes the use of composites with nanoscale inclusions of zirconia as a material for the preparation of metalfree dental prostheses. To check this possibility, alumina matrix nanocomposites samples were prepared with 5% of nanometric inclusions of ZrO2 to test the biocompatibility in vivo and some mechanichal properties. In the mechanical characterization tests were performed under 3 point bending (according to ISO 6872/97) and diametral tensile test. Biocompatibility tests were performed on bone and subconjunctival tissue of rats. The results showed that, in accordance with the standards in dentistry and compared with values observed in previous studies, the material in this study has excellent mechanical properties and excellent biocompatibility which allows its use as reinforcement in metal-free dental prostheses.